2011
DOI: 10.1002/rcm.5313
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying instantaneous regeneration rates of plant leaf waxes using stable hydrogen isotope labeling

Abstract: Leaf waxes protect terrestrial plants from biotic and abiotic stresses and are important sedimentary biomarkers for terrestrial plants. Thus, understanding the production and ablation of leaf waxes is critical in plant physiology and for geochemical studies. However, there have been no accurate approaches to quantify leaf wax production at different time scales. In this study, we demonstrate a novel approach to study leaf wax regeneration by irrigating plants with a pulse of deuterium-enriched water, followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 29 publications
(42 reference statements)
5
72
0
1
Order By: Relevance
“…Both controlled greenhouse experiments (14) and field experiments (19,20) support that the idea that the δ 2 H n-alkane values of grass leaf-wax n-alkanes reflect a continuous growth process. These studies show that the δ 2 H n-alkane values of grasses vary with the δ 2 H values of source and leaf water (14,19,20). This pattern supports the hypothesis that the δ 2 H n-alkane values of grass leaf waxes reflect the leaf-water environment during leaf expansion.…”
Section: In Deciduous Species δ 2 H Values Reflect Plant Environment mentioning
confidence: 57%
See 1 more Smart Citation
“…Both controlled greenhouse experiments (14) and field experiments (19,20) support that the idea that the δ 2 H n-alkane values of grass leaf-wax n-alkanes reflect a continuous growth process. These studies show that the δ 2 H n-alkane values of grasses vary with the δ 2 H values of source and leaf water (14,19,20). This pattern supports the hypothesis that the δ 2 H n-alkane values of grass leaf waxes reflect the leaf-water environment during leaf expansion.…”
Section: In Deciduous Species δ 2 H Values Reflect Plant Environment mentioning
confidence: 57%
“…Environmental and climate transect studies have shown that δ 2 H values of higher plant n-alkanes and environmental waters are correlated (9,10), but temporal observations of δ 2 H values of n-alkanes have produced conflicting data on the nature of this relationship (11)(12)(13)(14)(15) that require clarification to elucidate how δ 2 H values of ancient n-alkanes can be interpreted. To reconcile these issues and to provide the critical constraints for climate reconstructions using δ 2 H values of n-alkanes, carefully designed and controlled biologic experiments are needed that consider plant physiology and phenology (1).…”
mentioning
confidence: 99%
“…Another important and unresolved aspect of research seeking to understand the drivers of δ 2 H wax values is the timing of n-alkane synthesis in the growing season and associated growing season effects on δ 2 H wax (Kahmen et al, 2011a, Tipple et al, 2013, Gao et al, 2012b, Gao et al, 2012a, Sachse et al, 2010. Studies using controlled growth experiments of grasses (Mcinerney et al, 2011), as well as isotope labeling experiments on both Populus trichocarpa seedlings (Kahmen et al, 2011a) and mature Fraxinus americana leaves (Gao et al, 2012b) indicate that hydrogen isotopic compositions of n-alkanes stabilize shortly after leaf expansion at the beginning of the growing season and change very little thereafter.…”
Section: Introductionmentioning
confidence: 99%
“…Long-chain fatty alcohols are major constituents of the epicuticular wax layer (Samuels et al, 2008). Remarkably, recent studies have indicated that the constituents of this layer (including fatty alcohols) are actively turned over and that neither chemical conversion within the epicuticular layer nor erosion/evaporation can account for their loss (Jetter and Schäffer, 2001;Gao et al, 2012). Therefore, it is possible that fatty alcohols, recycled from the epicuticular layer, are continually being degraded in epidermal cells of aerial plant tissues by an oxidation pathway that might rely on FAO and FADH.…”
Section: Discussionmentioning
confidence: 99%